(EMIm)+(PF6)− Ionic Liquid Unlocks Optimum Energy/Power Density for Architecture of Nanocarbon‐Based Dual‐Ion Battery. Issue 24 (30th August 2016) - Shi, Xiaoyuan; Zhang, Wei; Wang, Jiafu; Zheng, Weitao; Huang, Keke; Zhang, Hengbin; Feng, Shouhua; Chen, Hong
Abstract : A delicate configuration of dual‐ion battery is proposed to achieve optimum energy/power density. High potential intercalation reaction of positive electrode contributes to high energy density and quick absorption/desorption of negative is beneficial for power density. Such novel designed electrochemical energy storage device enables access to optimum power/energy density.